Adipose-derived mesenchymal stem cells and retinal pigment epithelial cells interactions in a stress environment via tunneling nanotubes - Merve Gozel; Karya Senkoylu; Cem Kesim; Murat Hasanreisoglu (PLoS ONE, 2025)
This study aims to demonstrate the formation of tunneling tubes (TNTs) between adipose-derived mesenchymal stem cells (AdMSCs) and retinal pigment epithelial cells (RPE-1) and their alterations in response to experimental stress conditions. Serum starvation was employed as a stress condition to induce TNTs between the AdMSC and RPE-1 cells. The presence of TNTs was demonstrated through immunofluorescence microscopy, while scanning electron microscopy was utilized to determine the average thickness. Cell viability was assessed after stress by CellTiter-Glo, and H2DCFH-DA probes evaluated the cells’ reactive oxygen species (ROS) levels. Further, JC-1 labelled mitochondrial exchange between cells via TNTs was confirmed by time-lapse imaging. A transmembrane culture system was employed to inhibit TNTs. In this study, we investigated the role of TNTs in facilitating intercellular communication and mitochondrial transfer between AdMSCs and RPE-1 cells under stress. We found that TNT-mediated mitochondrial transfer from AdMSCs to RPE-1 helps to reduce ROS levels and improve cell viability. We demonstrated that direct interaction between AdMSCs and RPE-1 cells was crucial for stress recovery. Co-culture enhanced the viability and sustained the RPE-1 cells’ function after stress-induced damage. Mechanical inhibition of TNT formation decreased cell viability and elevated ROS levels, indicating the importance of TNTs in cellular protection. The findings can provide a new perspective on the therapeutic potential of stem cell-based therapy in protecting retinal pigment epithelium cells against stress-induced damage and promoting tissue regeneration.